Discover Windows 3.1 multimedia - Jennings, Roger (Carmel, Indiana : Que Corporation, 1992)
Provides a comprehensive introduction to and survey of multimedia. Presents strategies for incorporating sound, from the simple to the sophisticated. Includes a glossary of multimedia terms and concepts, plus how to incorporate sound and graphics into document.
I. The multimedia functions of Window 3.1 -- II. Using sound in Windows -- III. Musical synthesis and MIDI -- IV. Digital audio techniques -- V. Adding multimedia graphics -- VI. Authoring multimedia productions -- VII. Multimedia programming techniques -- Index.
Includes index.
Keywords: MICROSOFT WINDOWS (COMPUTER FILE)